THE EFFECT OF GREEN MARKETING ON BRAND IMAGE AND ITS IMPACT ON PURCHASE DECISIONS FOR EIGER PRODUCTS IN BANDUNG CITY - Selna Moh Triwidarto; Erna Maulina; Arianis Chan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to explore the impact of sustainable (green) marketing strategies on brand image and purchasing decisions among Generation Z consumers of EIGER products in Bandung City. Using a quantitative approach with SEM-PLS analysis through the SmartPLS 3.0 application, the research involved a minimum of 100 respondents located on Jl. Sumatera, Bandung. The findings indicate that green marketing strategies significantly influence brand image (O = 0.877) and purchasing decisions (O = 0.318). Brand image also has a significant effect on purchasing decisions (O = 0.636), and acts as a crucial mediator between green marketing and purchase decisions (O = 0.557). This study contributes to the literature on green marketing and consumer behavior, particularly in the context of Generation Z. It recommends that companies consistently apply sustainable marketing strategies to build a strong brand image and boost purchase intentions among younger consumers. The study is limited in geographic scope and brand focus, suggesting the need for future research to expand coverage and include various brands to enhance generalizability.